Impact of neonatal hyperbilirubinemia on peripheral neuromuscular development: evidence from muscle fiber conduction velocity measurements - Wang, Kun; Zhao, Wei; Song, Ling; Feng, Yeying; Kou, Qiuyue; Wang, Tieyan (Frontiers in Pediatrics, 2026)
BackgroundNeonatal hyperbilirubinemia is a common condition that may impair neurodevelopment, yet its impact on peripheral neuromuscular function remains underexplored.ObjectiveThis study aimed to assess the effects of hyperbilirubinemia on muscle fiber conduction velocity (MFCV) in neonates using surface electromyography (sEMG).MethodsMFCV was estimated from tibialis anterior sEMG recordings during passive and isometric contractions in neonates with and without hyperbilirubinemia. Global and local time-delay strategies were applied. Z-score analysis and repeated-measures ANOVA were used to compare groups, while regression analysis examined MFCV temporal trends.ResultsThe hyperbilirubinemia group exhibited significantly lower MFCV and Z-score values than controls (p < 0.001). Control infants showed characteristic spatial and temporal MFCV patterns, including arch-shaped conduction profiles and time-dependent declines, which were absent in the hyperbilirubinemia group. Disorganized innervation zone (IZ) distributions and reduced conduction variability further indicated impaired neuromuscular development.ConclusionsNeonatal hyperbilirubinemia may alter peripheral neuromuscular maturation. sEMG-based MFCV estimation may serve as a potential sensitive and noninvasive electrophysiological biomarker for detecting bilirubin-related neuromuscular impairment in early infancy.